INTEGRATED STUDY OF MODE OF ACTION OF MOCHARASA BASTI IN GRAHANI VYADHI WITH SPECIAL REFERENCE TO INFLAMMATORY BOWEL DISEASE (AYUSHDHARA, 2017)
During medical practice physician many times come across such diseases which are difficult to treat and one of them is Grahani. All the clinical features of Grahani Vyadhi resemble with ‘inflammatory bowel disease’. It is a broad term which indicates chronic inflammatory pattern of colon and thus also includes Ulcerative colitis and Crohn’s disease. Ulcerative colitis and Crohn’s disease both involve diarrhoea, pain in abdomen, fatigue, rectal bleeding and chronic persistence of disease results into weight loss. Crohn’s disease affects small intestine, large intestine, mouth, stomach and anus as well, but in Ulcerative colitis it mainly affects colon and rectum. Inflammatory bowel syndrome may develop at any age but 15-30 years is the most common age group getting affected. The therapeutic approach towards these diseases remains symptomatic in current mainstream line of treatment and has no prompt treatment as such. According to Madhava Nidana compendia which describe Grahani vyadhi with reference to organ Grahani, where regular function of Grahani sthana (organ) gets impaired. Grahani is the prime location of Agni, Pachaka pitta dosha, and Samana vayu. According to Ayurveda clinical presentation of Grahani Vyadhi very closely depicts picture of Inflammatory Bowel Disease as mentioned above. Acharya Charaka has described Mochrasa (extract of plant Bombax ceiba Linn. rich in tannins) as one of the medication for Grahani Vyadhi. Tannin-polysaccharide complex protects ulcerated areas of colon. It has been proposed here that a Mocharasa can to be used with milk as a Basti (medicated enema) preparation in patients with IBD.